Finite‐Element Analysis of Porosity Closure by Heavy Reduction Process Combined with Ultra‐Heavy Plates Rolling. Issue 11 (25th April 2014) - Zhao, Xinkai; Zhang, Jiongming; Lei, Shaowu; Wang, Yuanning
<x xml:space="preserve">Abstract</x> Limited by reduction radio, ultra‐heavy plates manufactured from slabs are always subjected to deterioration of soundness. For overcoming these defects, a new approach named heavy reduction process was presented. According to real production condition, a two‐step strategy was preceded using THERCAST3D to obtain the information of solidification firstly. Then, a special forging product FORGE3D had been used to simulate the heavy reduction and ultra‐heavy plates rolling. Results showed that the spheroidal porosity void can be formed into ellipsoidal body, but far from closure in the process of heavy reduction. Interestingly, the relationship between porosity void aspect ratio and closure evaluation index was independent of initial porosity void size and the reduction intensity. Furthermore, there was excellent correlation between equivalent strain and the porosity void aspect ratio. Results of such studies provided some valuable information on the optimization or design process of heavy reduction and rolling schedule for ultra‐heavy plates production.